Ketegangan permukaan dan aktivitas penghambatan tirosinase in vitro pada minyak tamanu (Calophyllum inophyllum L.) - Kusnaedi, Anggi; Andrianto, Dimas; Syaefudin (Buitenzorg: Journal of Tropical Science, 2024)
Tamanu or nyamplung oil, derived from Calophyllum inophyllum L., is commonly used in traditional medicine and occasionally used as a moisturizer in skincare cosmetics. In silico predictions suggested that tamanu oil contained compounds capable of inhibiting tyrosinase activity. This study aimed to measure the surface tension of tamanu oil and evaluate its tyrosinase inhibitory activity in vitro. The surface tension of tamanu oil was measured using the du-Nouy ring method with a tensiometer, while tyrosinase inhibitory activity was assessed by spectrophotometry using a microplate reader. The study revealed that the surface tension of tamanu oil was measured at 41.83±0.76 mN/m, and the tyrosinase inhibitory activity of tamanu oil was determined to be 83.75±0.41%. Notably, the inhibitory activity of tamanu oil was comparable to that of the positive control, kojic acid, which exhibited a tyrosinase inhibition of 84.59±2.04%. We concluded that tamanu oil has potential as a natural surfactant raw material and may serve as an effective tyrosinase inhibitor.   Keywords: Calophyllum inophyllum L., nyamplung, surface tension, tamanu oil, tyrosinase inhibitor